Analysis of Woody Vegetation in a High Elevation Oak Forest of Central Himalaya - Pathak, M. C.; Bargali, S. S.; Rawat, Y. S. (Indian Forester, 1993)
A quantitative analysis of woody vegetation in 12 stands of four aspects within an elevational range of 2100-2700 m in Central Himalaya was made. Q. floribunda exhibited absolute dominance in all the aspects. R. arboreum; I. dipyrena and Q. semecarpifolia were major associates. The total tree basal area ranged from 3898 to 5733 cm2/100 m2 and diversity and concentration of dominance of total vegetation from 2.180 to 2.649 and 0.014 to 0.155, respectively.